Presentation, medical complications and development of gestational trophoblastic neoplasia of hydatidiform mole after intracytoplasmic sperm injection as compared to hydatidiform mole after spontaneous conception - a retrospective cohort study and literature review - Braga, Antonio; Andrade, Taiane; do Carmo Borges de Souza, Maria; Campos, Vanessa; Freitas, Fernanda; Maestá, Izildinha [UNESP]; Sun, Sue Yazaki; Pedrotti, Luana Giongo; Bessel, Marina; Junior, Joffre Amim; Filho, Jorge Rezende; Elias, Kevin M.; et al. (Elsevier, 2023)
Objective: To describe the natural history of hydatidiform mole (HM) after intracytoplasmic sperm injection (ICSI), emphasizing the clinical and oncological outcomes, as compared to patients who had HM after spontaneous conception (SC). Study design: Retrospective historical cohort study of patients with HM followed at the Rio de Janeiro Federal University, from January 1st 2000-December 31st 2020. Results: Comparing singleton HM after SC to those following ICSI there were differences in terms of maternal age (24 vs 34 years, p < 0.01), gestational age at diagnosis (10 vs 7 weeks, p < 0.01), preevacuation human chorionic gonadotropin levels (200,000 vs 99,000 IU/L, p < 0.01), occurrence of genital bleeding (60.5 vs 26.9%, p < 0.01) and hyperemesis (23 vs 3.9%, p = 0.02) at presentation, and time to remission (12 vs 5 weeks, p < 0.01), respectively. There were no differences observed in the cases of twin mole, regardless of the form of fertilization that gave rise to HM, except molar histology with greater occurrence of partial hydatidiform mole (10.7 vs 40.0%, p = 0.01) following ICSI. Univariate logistic regression for occurrence of postmolar GTN after ICSI identified no predictor variable for this outcome. However, after adjusting for maternal age and complete hydatidiform mole histology, multivariable logistic regression showed the risk of GTN with HM after ICSI had an adjusted odds ratio of 0.22 (95%CI:0.05–0.93, p = 0.04), suggesting a possible protective effect when compared to HM after SC. Conclusions: Singleton HM after ICSI are diagnosed earlier in gestation, present with fewer medical complications, and may be less likely to develop GTN when compared with HM after SC.
Keywords: Assisted reproductive techniques; Gestational trophoblastic disease; Gestational trophoblastic neoplasia; Human chorionic gonadotropin; Hydatidiform mole; Intracytoplasmic sperm injection